The Political Economy of Sino-American Relations : A Greater China Perspective - Kueh, Y. Y.; Bridges, Brian, 1948- (Book collections on Project MUSE., 1997)
This volume draws on a wide range of international expertise to examine the nature of the US economic interaction with Greater China.